RELATIONSHIP OF THE FASN GENE POLYMORPHISM WITH MILK PRODUCTION AND ITS COMPONENTS IN LOCAL AWASSI SHEEP - Y. A. Almaamory; N. N. Al-Anbari (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was conducted to detecting the FASN gene polymorphism and its relationship to daily milk yield (DMY), lactation period, and milk composition in addition to polymorphism distribution and allele frequency in 52 Awassi ewes and their lambs. It was carried out from 5/1/2022 to 30/10/2022 at the Sheep Farm of the Al-Fayhaa station in the Jableh sub-district / Al-Musaib project (55 km south of Baghdad), in addition to the Biotechnology Laboratory at the College of Agricultural Engineering Sciences/University of Baghdad. Three polymorphism appeared in this variant (A>G SNP), which are AA, AG, and GG, with the percentages of 63.46, 32.69, and 3.85%, respectively. The variation among them were highly significant (P≤0.01) with a frequency of 0.70 and 0.30 for alleles G and A, respectively. The protein content of Awassi sheep’s milk differ significantly (P≤0.05) at rate 5.17% for ewes with GG polymorphism. In conclusion, FASN gene can be used to develop strategies for genetic improvement of sheep, and expanding the study to a larger sample and multiple sites and study the types of fatty acids in milk, as well as finding the interaction between two SNPs, would give more accurate results and determine the best method for managing and improving sheep flocks.